Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải:
a)
\(f(0)=\frac{-0}{2}+3=3\)
$f(1)=\frac{-1}{2}+3=\frac{5}{2}$
$f(-1)=\frac{-(-1)}{2}+3=\frac{7}{2}$
$f(2)=\frac{-2}{2}+3=2$
$f(6)=\frac{-6}{2}+3=0$
$f(\frac{1}{2})=\frac{-\frac{1}{2}}{2}+3=\frac{11}{4}$
b)
\(f(x)=2x-3\Rightarrow f(x+1)=2(x+1)-3=2x-1\)
Do đó: \(f(x+1)-f(x)=2x-1-(2x-3)=2\)
c)
\(f(2)=3.2-9=-3\)
\(f(-2)=3(-2)-9=-15\)
\(g(0)=3-2.0=3\)
\(g(3)=3-2.3=-3\)
a: \(f\left(2\right)=\dfrac{2-2}{\left(2+1\right)^2}=0\)
\(f\left(0\right)=\dfrac{0-2}{\left(0+1\right)^2}=-2\)
\(f\left(-2\right)=\dfrac{-2-2}{\left(-2+1\right)^2}=-4\)
b: \(f\left(3\right)=2\left|3-1\right|+3\cdot3-2=4-2+9=11\)
\(f\left(-2\right)=2\left|-2-1\right|+3\left|-2\right|-2=6+6-2=10\)
\(f\left(-1\right)=2\left|-1-1\right|+3\left|-1\right|-2=2\cdot2+3-2=5\)
Câu 1:
a)
\(y=f\left(x\right)=2x^2\) | -5 | -3 | 0 | 3 | 5 |
f(x) | 50 | 18 | 0 | 18 | 50 |
b) Ta có: f(x)=8
\(\Leftrightarrow2x^2=8\)
\(\Leftrightarrow x^2=4\)
hay \(x\in\left\{2;-2\right\}\)
Vậy: Để f(x)=8 thì \(x\in\left\{2;-2\right\}\)
Ta có: \(f\left(x\right)=6-4\sqrt{2}\)
\(\Leftrightarrow2x^2=6-4\sqrt{2}\)
\(\Leftrightarrow x^2=3-2\sqrt{2}\)
\(\Leftrightarrow x=\sqrt{3-2\sqrt{2}}\)
hay \(x=\sqrt{2}-1\)
Vậy: Để \(f\left(x\right)=6-4\sqrt{2}\) thì \(x=\sqrt{2}-1\)
a,
\(f\left(0\right)=2.0^2-3.0+5=0-0+5=5\)
\(f\left(-2\right)=2.\left(-2\right)^2-3\left(-2\right)+5=2.4+6+5=8+6+5=19\)
\(f\left(\sqrt{3}\right)=2\left(\sqrt{3}\right)^2-3\sqrt{3}+5=2.3-3\sqrt{3}+5=11-3\sqrt{3}\)
b, \(2x^2-3x+5=4\Leftrightarrow2x^2-3x+1=0\)
\(\Delta=\left(-9\right)^2-4.2=81-8=73>0\)
\(x_1=\frac{3+\sqrt{73}}{4};x_2=\frac{3-\sqrt{73}}{4}\)
f(x)=x :))
làm sao vậy bạn